A dataset from bottom trawl survey around Taiwan - Shao, Kwang-Tsao (Pensoft Publishers, 2012)
Abstract. Bottom trawl fishery is one of the most important coastal fisheries in Taiwan both in production and economic values. However, its annual production started to decline due to overfishing since the 1980s. Its bycatch problem also damages the fishery resource seriously. Thus, the government banned the bottom fishery within 3 nautical miles along the shoreline in 1989. To evaluate the effectiveness of this policy, a four year survey was conducted from 2000–2003, in the waters around Taiwan and Penghu (Pescadore) Islands, one region each year respectively. All fish specimens collected from trawling were brought back to lab for identification, individual number count and body weight measurement. These raw data have been integrated and established in Taiwan Fish Database (http://fishdb.sinica.edu.tw). They have also been published through TaiBIF (http://taibif.tw), FishBase and GBIF (website see below). This dataset contains 631 fish species and 3,529 records, making it the most complete demersal fish fauna and their temporal and spatial distributional data on the soft marine habitat in Taiwan.